Morphology and In Vitro Behavior of Electrospun Fibrous Poly(D,L-lactic acid) for Biomedical Applications - Toshihiro Inami; Yasuhiro Tanimoto; Masayuki Ueda; Yo Shibata; Satoshi Hirayama; Masaru Yamaguchi; Kazutaka Kasai (Advances in Materials Science and Engineering)
This work describes the fabrication, optimization, and characterization of electrospun fibrous poly(D,L-lactic acid) (PDLLA) for biomedical applications. The influences of the polymer concentration of the electrospinning solution (5, 10, or 15 wt%) and the solution flow rate (0.1, 0.5, 1.0, or 2.0 mL/h) on the morphology of the obtained fibrous PDLLA were evaluated. The in vitro biocompatibility of two types of PDLLA, ester terminated PDLLA (PDLLA-R) and carboxyl terminated PDLLA (PDLLA-COOH), was evaluated by monitoring apatite formation on samples immersed in Hanks’ balanced salt (HBS) solution. 15 wt% polymer solution was the most beneficial for preparing a fibrous PDLLA structure. Meanwhile, no differences in morphology were observed for PDLLA prepared at various flow rates. Apatite precipitate is formed on both types of PDLLA only 1 day after immersion in HBS solution. After 7 days of immersion, PDLLA-COOH showed greater apatite formation ability compared with that of PDLLA-R, as measured by thin-film X-ray diffraction. The results indicated that the carboxyl group is effective for apatite precipitation in the body environment.